Strategi Konvergensi Media Solopos: Kajian Teori Konstruksi Sosial - Diandra Aji (Universitas Sebelas Maret (UNS), 2025)
The Globalization Era encourages PT. Solopos to transform from print to digital media through mass media convergence, which gives rise to new social constructions in society. This study aims to analyze the social construction and Solopos strategy in facing media convergence in Surakarta City. The method used is qualitative with interview techniques, observation, and literature studies. The theory used is Berger and Luckmann's social ecological construction and media. The results of the study show that Solopos forms social construction through multi platform transformation, technology adaptation, and strengthening social roles. The strategies include changing work models, media diversification, and improving human resources. Internal and external dimensions such as work culture, technology, and audience expectations also influence this convergence process. The strategies implemented have an impact on content, production, work culture, interaction with readers, and public trust.